LEGAL PROBLEMS OF TAX INCENTIVES PRIVATES PENSIONS IN THE RUSSIAN FEDERATION - Zhuravleva, Оксана Олеговна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
In this article the author analyses the problem of legal regulation of tax incentives for the development of private pensions in the Russian Federation as well as the related problems of the principle of fairness of taxation, stability and respect for the rights and interests of the citizens, changes in patterns of pension provision.